Quantification of interlinked environmental footprints on a sustainable university campus: A nexus analysis perspective. (15th July 2019) - Gu, Yifan; Wang, Hongtao; Xu, Jin; Wang, Ying; Wang, Xin; Robinson, Zoe P.; Li, Fengting; Wu, Jiang; Tan, Jianguo; Zhi, Xing
Highlights: A quantitative nexus analysis method based on environmental footprints is proposed. A university case study has been selected as analogous to an independent community. The environmental impacts of campus operations and food procurement are analyzed. The nexus across the energy, water, food, waste and carbon emission are discussed. Policy suggestions are provided based on the findings from the nexus analysis. Abstract: Developing a nexus approach to the quantitative analysis of different environmental sectors including energy, water and carbon emissions is important for promoting integrated sustainable management at a community scale. Universities can be considered small communities in themselves, providing access to data at the community scale, as well as contributing to global sustainability through their education, research and the operation of their own estate. In this study, we developed a conceptual nexus analytical framework based on the combination of different environmental footprints to assess how universities, as an example of a small community, interact with the hydrological cycle, energy resources and climate, through their operations and food procurement. Using Keele University in the United Kingdom as an example, the total energy footprint, carbon footprint and water footprint in the 2015/16 academic year was 42, 202 MWh, 14, 393 tonnes of CO2 e and 532, 415 m 3 . Through the quantification of these interlinked environmental footprints, the nexus across water, energy, waste disposal, food procurement, and corresponding carbon emissions at Keele University have been explored. Based on the results of the nexus analysis and identifying the areas of greatest environmental benefit studied, policy suggestions are provided including: implementing energy control systems; maximising the development of wind energy and solar photovoltaic; increasing the availability of vegetable-based options in food procurement decisions; and collecting all of the food waste for anaerobic digestion. The findings serve as a reference for policy-makers and practitioners making decisions on the basis of sustainability in universities and other communities.